Sensory Analysis of Three Teflon Toast Bread Variants Based on Organoleptic Tests and Hedonic Tests - Rofendi, Hawa Auliya; Nur Qomariyah, Umi Kulsum (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
Teflon toast is a popular food product and continues to grow in Indonesia. This study aims to analyze three variants of Teflon toast with different sugar levels using organoleptic tests and hedonic tests. Three variants of bread are made with different sugar levels, namely 20 grams, 15 grams and 10 grams. Ten panelists were involved in the assessment of organoleptic characteristics and analysis of variance (ANOVA) was used to evaluate differences between the three variants. The results showed that there were no significant differences in organoleptic characteristics between bread variants (p > 0.05). The hedonic test also confirmed that all bread variants received similar levels of liking from the panelists. Thus, variations in sugar content in Teflon toast did not provide a significant difference in sensory aspects.